Literasi Media Online pada Kalangan Remaja Untuk Meningkatkan Pemahaman Etika Berkomunikasi di Media Sosial - Denada Faraswacyen L. Gaol; Indah Suryawati; Rachmi Kurnia Siregar; Dudi Iskandar (IKRA-ITH ABDIMAS, 2023)
The Nahdlatul Ulama Student Association (IPNU) is an autonomous body of Nahdlatul Ulama (NU)based on students, students, and santri, as a forum for fostering the next generation of scholars andsuccessors of the nation's struggle. IPNU is an organization whose members are millennials (generation Y)and generation Z. The organization certainly has problems faced, one of which is related to the ethics ofcommunicating on social media by the younger generation of IPNU Ciledug. From one of the problemsfaced by IPNU, a Community Service activity was designed by Communication Studies Lecturers at BudiLuhur University with the title Online Media Literacy among Adolescents as an Effort to ImproveUnderstanding of Communication Ethics in Social Media. This activity can be useful as a means of learningfor the younger generation at IPNU Ciledug to be able to apply communication ethics in online media after understanding online media literacy in accordance with the planned program and in accordance with theexpected target. The output targets to be achieved from this community service activity are: (1)Implementation documentation in the form of activity videos; (2) Articles in PKM journals; (3) Increasedknowledge, abilities, skills of IPNU Ciledug members in understanding the ethics of communicating onsocial media. The implementation of this community service activity consists of 3 stages, namely; (1) Thepreparation stage, to identify problems, apply for permits to the IPNU Ciledug management, and makepreparations for the implementation of online media literacy activities; (2) the implementation stage ofonline media literacy activities; and (3) the activity evaluation stage, by giving a questionnaire to thetraining participants to find out the response of IPNU Ciledug to this community service activity.